Holter Monitoring in assessing Cardiac Arrhythmias in Symptomatic Patients: A Prospective Observational Study - Karki, Biplave; Ghimire, Jeet; Nepal, Bikash; Mahaseth, Aditya; Sah, Ajit; Pandit, Swapnil; Pandey, Naveen; Shah, Prashant; Karki, Prahlad (Nepal Mediciti Medical Journal, 2022)
BACKGROUND The 24hr ECG Holter monitoring system is helpful in assessing cardiac arrhythmias in patients presenting with palpitation, dizziness, presyncope and syncope, which are not detected by standard office electrocardiogram. METHODS This was a single center prospective observational study conducted to assess the prevalence of cardiac arrhythmias among 78 patients consisting of 41 males and 37 females referred for 24 hr ECG Holter monitoring in BPKIHS, Dharan, Nepal, between October 2021 to December 2021. RESULTS The most common indication for 24 hr ECG Holter monitoring in these patients was unexplained palpitation. Ventricular ectopics were the most common arrhythmias detected, followed by supraventricular ectopics, most of which were benign. Among 18 patients with significant bradyarrhythmia, 3 had sinus bradycardia with significant pause, 3 had AF with significant pause, and 2 had high grade/complete AV block. CONCLUSIONS The study showed that most of the arrhythmias detected are benign and prevalence of potentially fatal ventricular and supraventricular tachyarrythmias are relatively low in our population.